1989
DOI: 10.1111/j.1365-2125.1989.tb03500.x
|View full text |Cite
|
Sign up to set email alerts
|

EEG brain mapping in evaluating the time‐course of the central action of DUP 996‐a new acetylcholine releasing drug.

Abstract: Computer-assisted spectral analysis of the EEG and subsequent topographic brain mapping of the drug-induced EEG changes demonstrated significant central effects of DUP 996 suggesting vigilance-improving properties. The findings were characterized mostly by an augmentation of total power as well as by an increase of absolute power in the alpha and alpha-adjacent beta activity. 4 Time-course investigations demonstrated two pharmacodynamic peaks: a first one in the 2nd h and a second one in the 12th h. In detail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(10 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…In our study, systemic pressure was unchanged or even decreased at the highest dose of linopirdine. We cannot explain the discrepancy, but our findings concur with reports that linopirdine does not affect blood pressure in humans (Saletu et al, 1989;Pieniaszek et al, 1995).…”
Section: Discussionsupporting
confidence: 41%
“…In our study, systemic pressure was unchanged or even decreased at the highest dose of linopirdine. We cannot explain the discrepancy, but our findings concur with reports that linopirdine does not affect blood pressure in humans (Saletu et al, 1989;Pieniaszek et al, 1995).…”
Section: Discussionsupporting
confidence: 41%
“…Results of electroencephalograms, ECGs, and clinical laboratory evaluations were not affected (Pieniaszek et al, 1995). Another study administering single oral doses of 30 mg linopirdine observed electroencephalography changes suggesting vigilance-improving properties and no abnormalities in ECG or laboratory evaluations, indicating a good tolerability (Saletu et al, 1989). Although the highest plasma levels were approximately 1.5 mM in those experiments compared with 10 mM of linopirdine in our in vitro experiments, this indicates a potential for clinical use of K V 7 blockers.…”
Section: Discussionmentioning
confidence: 65%
“…94 Linopirdine was regarded as a promising drug because it enhanced the release of acetylcholine in cholinergic nerve terminals in the brain only when its release was triggered and improved learning and memory in rodents and primates. Although clinical trials with linopirdine remained largely inconclusive 95 or showed that it did not improve memory performance in elderly subjects, 96 linopirdine became a valuable pharmacological tool.…”
Section: K V 7 Channel Blockersmentioning
confidence: 99%